Trigeminal Neuralgia due to an Isolated Cerebral Varix: Case Report - Inoue, Takuro; Shima, Ayako; Hirai, Hisao; Suzuki, Fumio; Matsuda, Masayuki (Journal of Neurological Surgery Reports, 2014)
Intracranial isolated varix is a very rare entity. Although it is usually asymptomatic, there are reports on symptomatic cases with hemorrhage or mass effect that mostly relate to arteriovenous fistulas or arteriovenous malformations. We present an extremely rare case of trigeminal neuralgia caused by an isolated varix. A 55-year-old woman had been experiencing right trigeminal neuralgia for 3 years. Computed tomography and magnetic resonance imaging revealed an enhanced mass lesion on the root entry zone of the right trigeminal nerve. Angiograms confirmed the mass was a varix arising on the vein connecting the basal vein of Rosenthal and the superior petrosal vein. Preoperative three-dimensional (3D) imaging clearly depicted the anatomical relation of the varix, adjacent vessels, and trigeminal nerve, which helped plan operative procedures. The varix with its parent vein was successfully transposed from the nerve without sacrificing any veins. Her pain disappeared immediately after the surgery and did not recur during a 30-month follow-up period. The 3D image contributed to making an accurate and safer operative plan especially for this rare case.
Keywords: trigeminal neuralgia; developmental venous anomaly; varix; 3D imaging